Translation and cultural adaptation of the pectus excavatum evaluation questionnaire to Spanish and Catalan - Irene de Haro Jorge; Xavier Tarrado; Asteria Albert Cazalla; Natalie García-Smith; Alba Fernàndez-Candial; Carlos Salcedo-Gil (SpringerOpen, 2022)
Abstract Purpose Pectus excavatum (PE) is the most common congenital chest wall deformity. It can have a negative effect in exercise tolerance. However, cosmetic features are the most frequent concerns in these patients. The PE evaluation questionnaire (PEEQ) is a patient reported outcome (PRO) tool to measure the physical and psychosocial quality-of-life changes after surgical repair of PE. No specific tool has been developed in our languages to evaluate PRO in PE patients. Our aim is to translate and culturally adapt the PEEQ to Spanish and Catalan. Methods Guidelines for translation of PRO were followed. The PEEQ, consisting of 34 items, was translated from English to Spanish and to Catalan. Three forward translations and one back translation were performed for each language. Cognitive debriefing interviews were developed. Results The reconciliation of the forward translations revealed a 14.7% of inconsistencies for each language. The Spanish back translation showed a 64.7% of disagreement with the source, the Catalan 58.8%. Changes in each reconciled version were made to amend the diverting items. Cognitive debriefing: Catalan version: 15 participants, 10 males, 5 patients had been operated. 12 patients showed difficulties for understanding 4 of the items. Spanish version: 17 participants, 11 males, 5 had been operated. 13 patients showed difficulties for understanding 4 of the items. We made modifications of the problematic items, in order to make them easier to understand for our patients. We tested the last version in a new group of patients. Catalan: 7 patients, 5 males. One patient showed difficulties for understanding item 11, so we added a further clarification of this item. Spanish: 7 patients, all males. There were any difficulties for understanding. Conclusion After a thorough process of translation and cultural adaptation, we reached a Catalan and a Spanish version of PEEQ. This work constitutes the first step to reach a specific PE PRO tool in our languages. However, it needs to be validated, with a higher number of patients, before being widely used in a clinical setting.